The status of digital innovation and data security in South African Higher Education - Adeyemo, K. S. (South African Journal of Higher Education, 2023)
Most Higher Education Institutions (HEIs) in South Africa have moved teaching and learning to online platforms due to the COVID-19 pandemic. With this new development, the responsibility falls upon HEIs to ensure the security of their data. The policy expectation is that HEIs adopt innovative strategies to manage disruptions in teaching and learning processes. This article problematises digital innovation as a post-COVID strategy for data security in Higher Education (HE) in South Africa. It uses the Model of Enterprise Intelligence to make a case for digital innovation and the transformation of teaching and learning in South Africa. Within this conceptual framework, evidence from literature and the digital policies from 2004 to 2020 (see Table 1) were analysed to have a better understanding of digital innovation, collaboration, and transformation in South Africa. Methodologically, the article reviewed the literature, secondary data, and the South African policy document on National Digital and Future Skills Strategy (Notice 513 2020). The findings show that the status of digital innovation and data security in South African Higher Education need further review. More specifically, this review should be collaborative, eliminate a top-down approach to digital policy formulation and reduce the effect of inequality through an effective funding for poor students and institutions.